Aplicabilidade de índices colorimétricos no melhoramento genético da cana-de-açúcar (Saccharum spp.) - Tairum, Rachel Cruz Carvalho (Universidade Federal de São Carlos, 2020)
Modern techniques and equipment have proved to be of great value in accelerating the harvest and productivity of crops. This is due to precision agriculture that has evolved to improve the knowledge of the field, however, it is not only in the context of final production that the improvements can be observed but also in the development of varieties during the genetic improvement of plants, where techniques of Remote sensing has been used to better understand the field areas and the genetics of the individuals to be selected. To this end, the use of Unmanned Aerial Vehicles (UAVs) has proven to be of great value as a method of remote, accurate and rapid assessment of the field, incorporated with RGB cameras that are usually factory equipment with the UAV. However, in addition to the pure visualization of the images obtained, color indices can also be used for more detailed exploration of the plants. In the culture of sugarcane, works involving this type of approach are rare, mainly in convergence with genetic attributes, an area that has grown and may be better explored. Thus, the objective of this work was to study how the use of UAVs and color indices can be incorporated into the genetic breeding of sugarcane through the study of two areas: The Painel Brasileiro de Genótipos de Cana-de-Açúcar (PBGCA) and a second phase of selection of varieties (T2) in the genetic breeding program. With this study, it was possible to ascertain that the indices are correlated with each other, however they do not correlate with the field indices evaluated during the second improvement phase, observing a distinction between color indices and field indices. In the panel evaluation, it was possible to determine some ideal crop evaluation times, as well as the distinction between a rainy season, a dry period and a plant growth period. In general, the present dissertation can consider the use of color indices as a future tool to be incorporated in breeding programs for the selection of individuals, and the ExG color index was the most appropriate considering the components of variance and heritability. However, it was not yet possible to find associations with variables commonly used in the field, thus requiring further studies on the subject.
Application of color indices for sugarcane (Saccharum spp.) breeding
Keywords: VANT; ExG; VARI; T2; PBGCA; Herdabilidade; UAV; BPSG; Heritability; CIENCIAS AGRARIAS::AGRONOMIA